Respiratory Therapist-Driven Weaning Protocols from Mechanical Ventilation: A Systematic Review of Clinical Effectiveness - Alattas, Abubakr Mohsen; Qaari, Almutasim Billa Yahya Mohammed; Dhayihi, Riyadh Hamoud Mohammed; Ageeli, Asim Ali; Ageely, Ali Hussein; Tawhari, Bandar Hassan; Makharash, Taha Mohammed; Albogami, Nawaf Rageh; Kabi, Mofareh Ali; Althurwi, Khalid Ali; Alsaadi, Ibrahim Othman (Journal of Ecohumanism, 2024)
Background: Weaning from mechanical ventilation is a crucial and complex process in intensive care units (ICUs). Despite advancements, variability in weaning protocols exists, leading to inconsistent outcomes. Respiratory therapist (RT)-driven weaning protocols have been proposed as a solution to improve efficiency and patient outcomes. This systematic review aims to evaluate the clinical effectiveness of RT-driven weaning protocols compared to physician-directed strategies in mechanically ventilated patients.Aim: To assess the impact of RT-driven weaning protocols on key clinical outcomes such as mechanical ventilation duration, ICU length of stay, extubation success, and post-extubation complications, particularly focusing on respiratory failure and reintubation rates.Method: A systematic search of studies published between 2020 and 2024 was conducted using databases such as PubMed, Scopus, and Cochrane Library. Ten primary studies, including randomized controlled trials (RCTs) and cohort studies, were selected based on predefined inclusion criteria. Data were synthesized to evaluate the effectiveness of RT-driven protocols in ICU settings.Results: The review found that RT-driven protocols significantly reduced mechanical ventilation duration, shortened ICU length of stay, and increased extubation success rates compared to physician-directed protocols. Additionally, RT-driven protocols were associated with a reduction in post-extubation respiratory failure (PERF) and reintubation rates. However, the studies showed variability in implementation, patient populations, and outcomes. Conclusion: RT-driven weaning protocols are effective in improving patient outcomes, reducing ICU resource utilization, and enhancing the weaning process. Further research is needed to standardize these protocols, refine their implementation across diverse ICU settings, and explore their economic implications.